Importance of accurate measurement of carotid intima-media thickness for evaluating epileptic children treated with valproate - Ozkan, Fuat; Inci, Mehmet Fatih; Demir, Caner Feyzi (Springer, 2013)
[Abstract Not Available]
Keywords: Disease Risk; Atherosclerosis; Artery; Ultrasound